Key issues in Bata Pakistan Marketing Strategy - Hassan, Muzammal; Riaz, Hira; Munir, Imran; Noor, Qaisra (Advances in Social Sciences Research Journal, 2022)
In this case study, we discuss BATA’s marketing strategy and launching of higher segments in the Pakistan market without any research or decision. So BATA face many problems in past then re-launch and become successful after many hurdles. The reason why Bata become successful in the market is direct target market and direct contact with target customers and the most important factor is the direct research process.